Berçário como lugar : significações segundo profissionais de educação infantil das unidades de atendimento à criança de até três anos no município de Cuiabá - Silveira, Giovanna Lobianco (2013)
The current ethnographic like dissertation work aims to identify the shared significations of a group of early childhood development technicians working at the municipality daycare centers towards their understanding of the nursery as a workplace. This subject is taken as an indicator to provide access to these professionals’ identities particularly those that work with babies. In this context, the professional identity is build by social and historical events, thus considering the early childhood professional as a recent actor in the history of the teaching careers. Originally conceived as a caregiver place the daycare centers were destined for centuries to receive children from the poorest families. Currently this Institution represents the first stage of the basic educational process in Brazil. This way, this work is justified by the importance of understanding the processes that structure the identity of these professional particularly in a workspace that is very much attached to an assistentialist past. This work is mainly based in the Social Representation Theory (MOSCOVICI, 1978, JODELET, 2001), its dialogue with space related studies (JODELET, 1982; TUAN, 1980; ROSSETI-FERREIRA, 2009; CAMPOS-DE-CARVALHO, 2003, 2008), identity (DESCHAMPS & MOLINER, 2003) as well as studies about childhood education (HADDAD, 2009, CERISARA, 2002) and teacher´s identity (SARMENTO 1994, TARDIF, 2002). This study is presented in two sections. The methodological procedures related to the first section are free word association and semi-structured interviews. The second section is based in studies made in eight daycare centers that also provide nurseries and employed as methodological procedures the participant observation and semi-structured interviews. Data obtained by free word association were processed in the software Programmes Permettant l’Analyse des Evocations (EVOC) and its results subjected to analysis under the scope of the Central Nuclear Theory (ABRIC, 1998). Interviews were processed in the software Analyse Lexicale par Contexte d´um Esemble de Segments de Texte (ALCESTE), as well as its contents analysis. The group of professionals studied comprised 35 of the 70 people employed as Early Childhood development technician working in the eight daycare centers of Cuiabá-MT municipality. All subjects are of female genre with many degrees of professional education. The results show that the studied group considered the nursery social representation as a place for safekeeping and protection which is linked to the historical conceptualization of the daycare centers. Regarding the group shared significations of the early childhood professional takes back to the image of the second mother, which present characteristics of a competent babysitter. The image of a teacher of babies appears as an educator, preluding the new significances given to these professionals. It is possible to express that the early childhood technician profession lies in the tension between the significances obtained in the professional education centers and those significances that runs in the society, legitimated by the incongruences of the official documents and their real work conditions.